2017
DOI: 10.1111/ens.12230
|View full text |Cite
|
Sign up to set email alerts
|

Origins and implications of apid bees (Hymentopera: Apidae) in French Polynesia

Abstract: Island plant–pollinator networks are typically simpler than their continental counterparts and this can make them less resilient to disturbance from exotic species. French Polynesia has a very low diversity of bees, but their status as either native or introduced species has been largely speculative. We combine previous studies with new DNA sequence data to show that 11 bee species have now been recorded for French Polynesia. Haplotype variation at the ‘barcode’ region of the mitochondrial gene cytochrome c ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In the southwest Pacific islands of Fiji, Samoa, and Vanuatu, there is some evidence to indicate that most, if not all, apid and megachilid bees have been introduced by humans [26,64]. A similar situation likely exists in French Polynesia [39]. On the Hawaiian Islands, which likely have only 69 native bee species, there are 14 non-native bee species recorded [9,17].…”
Section: Non-native Bee Speciesmentioning
confidence: 99%
“…In the southwest Pacific islands of Fiji, Samoa, and Vanuatu, there is some evidence to indicate that most, if not all, apid and megachilid bees have been introduced by humans [26,64]. A similar situation likely exists in French Polynesia [39]. On the Hawaiian Islands, which likely have only 69 native bee species, there are 14 non-native bee species recorded [9,17].…”
Section: Non-native Bee Speciesmentioning
confidence: 99%
“…Concerns have been raised that the introduction of the buzzpollinating bee A. pulchra to Fiji may create problems because it could increase seed set in solanaceous weeds with poricidal anthers (Groom et al 2014a(Groom et al , 2017. However, Staines et al (2017) found that an endemic halictine Fijian bee was likely to affect pollination of the major pan-tropical weed, S. torvum, via pollen larceny.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Staines et al 2017) shows that the endemic bee Homalictus fijiensis is not a buzz-pollinator but is able to extract pollen from S. torvum by biting at anther tips and likely effects pollination when crawling over exerted styles, allowing pollen grains stored on metasomal scopae to come into contact with stigmas. Groom et al (2014aGroom et al ( , 2017 argued that the introduction of A. pulchra to Fiji may pose an ecosystem risk by increasing pollination rates of solanaceous weeds. Groom et al (2014aGroom et al ( , 2017 argued that the introduction of A. pulchra to Fiji may pose an ecosystem risk by increasing pollination rates of solanaceous weeds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations